Second language acquisition - Slabakova, Roumyana (Oxford University Press, 2016)
This textbook approaches second language acquisition from the perspective of generative linguistics. It reviews the last thirty years of research in the field, focussing in particular on how the second or additional language is represented in the mind and how it is used in communication